LOUIS-PHILIPPE AUDET AND HIS WORK - Boulianne, Réal (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1972)
It is difficult to appreciate the current state of Quebec society without understanding its past. Perhaps the idea of the past has dominated Quebec more than any other province in Canada. Indeed, the preservation of institutions and of a culture deeply rooted in hundreds of years of history seems to have been one of the major determinants in the evolution of Quebec society. Because education reflected this pre-occupation with the past, it is important to view its current development in the perspective of history. Unfortunately, until very recently there was rea1ly no comprehensive and objective survey of the history of education of Quebec, and much of what French Canadian historians had written was, as Marcel Lajeunesse has suggested, " ... pour glorifier leur ’alma mater,’ ajouter un argument à la mission essentiellement civilisatrice en Amerique du Nord ou élargir le champ des luttes nationales .... " Clearly there was need for a well documented and objective history of education in Quebec and in this context the publication of Louis-Philippe Audet’s Histoire de l’enseignement au Quebec, 1608-1971 (Montreal: Holt, Rinehart and Winston, 1971, Vol. I, 432 pp., Vol. Il, 496 pp., 24.95) marks a milestone in Quebec historiography.